Fusion of Freehand SPECT and Ultrasound to Perform Ultrasound-Guided Fine-Needle Aspiration Cytology of Sentinel Nodes in Head and Neck Cancer - de Bree, R.; Pouw, B.; Heuveling, D.A.; Castelijns, J.A. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Criteria for ultrasound-guided fine-needle aspiration cytology (USgFNAC) for the detection of occult lymph node metastasis in patients with clinically negative head and neck cancer are based on the morphology of cervical lymph nodes. To improve the selection of lymph nodes for USgFNAC, we examined the feasibility of fused freehand single-photon emission tomography ultrasound-guided fine-needle cytology (freehand SPECT-USgFNAC) of sentinel nodes in patients with early stage oral and head and neck skin cancer.MATERIALS AND METHODS: Six patients with early-stage head and neck cancer (4 oral and 2 head and neck skin cancers) and a clinically negative neck who were scheduled for transoral or local excision and a sentinel node procedure underwent USgFNAC and freehand SPECT-USgFNAC preoperatively.RESULTS: All freehand SPECT sonographic examinations were technically successful in terms of identifying sentinel nodes. All aspirates of sentinel nodes obtained by freehand SPECT-USgFNAC contained substantial radioactivity, confirming puncture of the sentinel nodes. USgFNAC evaluated 13 lymph nodes; freehand SPECT-USgFNAC, 19 nodes; and sentinel node biopsy, 13 nodes. Three sentinel nodes were histopathologically positive and were selected for aspiration cytology by freehand SPECT-USgFNAC, but not by conventional ultrasound. The cytologic examination findings of the aspirations were negative or inconclusive.CONCLUSIONS: Freehand SPECT ultrasound can identify sentinel nodes and could potentially improve USgFNAC in patients with head and neck cancer by better selection of lymph nodes at highest risk of having metastases (sentinel nodes), but its sensitivity is limited by sampling error and insufficient aspirated material for cytology.cN0clinically node-negativeOSCCoral squamous cell carcinomaSNsentinel nodeSNBsentinel node biopsyUSultrasoundUSgFNACultrasound-guided fine-needle aspiration cytology